Skeletonization Technique in Coronary Artery Bypass Graft Surgery Reduces the Postoperative Pain Intensity and Disability Index. Issue 1 (12th December 2013) - Bawany, Faizan Imran; Khan, Muhammad Shahzeb; Khan, Asadullah; Hussain, Mehwish
Abstract Background and Aim Benefits of the skeletonized internal thoracic artery (ITA) include increased graft flow, increased graft length, and reduced incidence of sternal complications. We conducted a randomized, double‐blinded comparison of skeletonized versus pedicled ITA to assess the differences in pain intensity and extent of disability between the two types of harvesting procedures at one and three months follow‐up. Methods A total of 50 patients were included in our study. Twenty‐five patients had undergone skeletonized grafting while the other half had undergone pedicled grafting. The patients were evaluated for their pain at one and three months postoperatively. Extent of disability was measured via Pain Disability Index and intensity of pain was measured via Visual Analogue Scale (VAS). The patients were also questioned about the details of their pain using Short Form McGill Pain Questionnaire. Results In the first month, the mean pain intensity measured through VAS was 30.4 ± 4.0 and 55.0 ± 5.7 mm in skeletonized and pedicle group, respectively. The pedicled group had significantly higher scores measured by all three scales at both one‐ and three‐month intervals (p‐values < 0.0001). Conclusions Our results indicate that skeletonization of ITA significantly reduces postcoronary artery bypass graft surgery pain at both one‐ and three‐month intervals. Long‐term clinical trials involving larger sample sizes should be conducted to fully confirm the benefits of the skeletonization technique. doi: 10.1111/jocs.12273 (J Card Surg 2014;29:47‐50)